2018
DOI: 10.1111/rda.13321
|View full text |Cite
|
Sign up to set email alerts
|

A study on ghrelin and LH secretion after short fasting and on ghrelin levels at perioestrual period in dairy cattle

Abstract: In two experiments, we studied (a) the changes of LH secretion in heifers under different feeding schedules and (b) total ghrelin concentration at oestrus in cows and heifers. In experiment one, synchronized heifers were allocated in three groups (R, regularly fed controls; F, fasted; and F-F fasted-fed). One day after the completion of the oestrous induction protocol, group F and F-F animals stayed without feed for 24 hr; thereafter, feed was provided to R and F-F cattle; 2 hr later, GnRH was administered to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
(64 reference statements)
0
3
0
1
Order By: Relevance
“…Moreover, others have reported that ghrelin concentration increased and LH concentration decreased when feed restricting cows and heifers but blood progesterone concentration did not change [33]. The restricted period implemented by Chouzouris et al [33] was shorter than the period used in Experiment I; but it had a similar time period as Experiment II. It is possible that in the bovine and ovine, blood progesterone concentration is not associated with plasma ghrelin concentration.…”
Section: Plos Onementioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, others have reported that ghrelin concentration increased and LH concentration decreased when feed restricting cows and heifers but blood progesterone concentration did not change [33]. The restricted period implemented by Chouzouris et al [33] was shorter than the period used in Experiment I; but it had a similar time period as Experiment II. It is possible that in the bovine and ovine, blood progesterone concentration is not associated with plasma ghrelin concentration.…”
Section: Plos Onementioning
confidence: 86%
“…The supraphysiological doses of ghrelin used in this study, however, may have contributed to the decrease in plasma progesterone concentration in the rats [ 32 ]. Moreover, others have reported that ghrelin concentration increased and LH concentration decreased when feed restricting cows and heifers but blood progesterone concentration did not change [ 33 ]. The restricted period implemented by Chouzouris et al [ 33 ] was shorter than the period used in Experiment I; but it had a similar time period as Experiment II.…”
Section: Discussionmentioning
confidence: 99%
“…Foi verificado que durante períodos de redução a matéria seca, a expressão do gene da grelina foi regulado positivamente (TENA-SEMPERE, 2007). Em um estudo com novilhas em jejum foi verificado que elevadas concentrações de grelina induzidas por situações de restrição alimentar podem afetar negativamente a secreção de LH, mesmo após a restauração da grelina aos valores basais (CHOUZOURIS et al, 2018). Embora a ação de neuropeptídios estejam relacionadas a ação da grelina, mais pesquisas precisam ser realizadas para melhor elucidar esse mecanismo.…”
Section: Grelinaunclassified
“…The hypothalamus, especially through its centers of hunger and satiety, controls ingestion by modulating various hormones, blood concentrations of various metabolites, and the autonomic nervous system. The causes of anorexia are the most diverse, and they can generate changes in the blood metabolic profile, which is frequently used in veterinary clinical diagnosis [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%